Como resolvo essa equação??
Y= 3x2-6x-1
Soluções para a tarefa
Respondido por
1
Baskara 6+-√∆/2.a.
6+-√48/6
2 raízes
6+√48/6 e 6-√48/6
∆=36-4.3(-1)
∆=36+12
∆=48
Respondido por
0
Se X não for elevado ao quadrado, aplica-se equação de primeiro grau
Anexos:
![](https://pt-static.z-dn.net/files/d03/8c00bcbaa2e323cc656edeb8997d17b7.jpg)
Perguntas interessantes
Biologia,
11 meses atrás
Geografia,
11 meses atrás
Física,
11 meses atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás